Multiwavelength Mid-Infrared Laser Generation Based on Optical Parametric Oscillation and Intracavity Difference Frequency Generation - Peng Wang; Yaping Shang; Xiao Li; Meili Shen; Xiaojun Xu (IEEE Photonics Journal)
We report a multiwavelength mid-infrared laser based on intracavity difference frequency generation in an MgO-doped periodically poled LiNbO3 optical parametric oscillator, which was pumped by a dual-wavelength fiber MOPA consisting of two parts: dual-wavelength seed and power amplifier. The maximum output power of the linearly polarized pump laser was 65.3 W, and the wavelengths were 1060 and 1080 nm. Three idler emissions with different wavelengths of 3127, 3303 and 3346 nm were obtained under the maximum pump power, and the total idler output reached 7.38 W, indicating a 15% pump-to-idler slope efficiency. The signal laser generated in the experiment had two wavelengths, which were 1594 and 1604 nm under the maximum pump power. Three nonlinear progresses occurred in the experiment, two of them being optical parametric oscillation and the one left being difference frequency generation.